Análise da expressão de orexina-A e B em neurônios ativados por CO2 no hipotálamo de ratos nas fases clara e escura do ciclo circadiano - Silva, Eliandra Nunes da (2019)
Orexinergic neurons (OX) located in the lateral hypothalamus (LH), lateral and medial perifornical area (LPeF/MPeF) and dorsomedial hypothalamus, through orexin-A or orexin-B, can exert influence on hypercapnic ventilatory responses, acting directly in respiratory control areas or modulating the activity of other chemossensitive sites. Despite the evidence about the role of orexinergic system in central chemoreflex, the differences in the activation of these neurons by CO2 in the light and dark phase of the circadian cycle, as well as the likely differential activation between the hypothalamic nuclei that contain these neurons, is poorly understood. In the present study, in Wistar rats submitted to normocapnic or hypercapnic conditions (7% CO2), immunohistochemical protocols evaluated the number of Fos, orexin-A, orexin-B and neurons that co-localize Fos with Orexin-A or B in the LH, LPeF, MPeF e DMH in the light and dark phase of the diurnal cycle. Quantitative analysis of the expression of immunoreactive neurons showed that hypercapnia causes an increase in the number of neurons expressing Fos protein in LH, LPeF, MPeF and DMH in the light and in the dark phase of the diurnal cycle. In addition, there was an increase of orexin-A in hypercapnia in the light phase in LH, while there was decrease of orexin-A in hypercapnia in the dark phase in LPeF, MPeF and DMH. Neurons that co-localize Fos and orexins augmented in both phases of the diurnal cycle in the LH, LPeF and DMH, whereas in the MPeF this increase was observed only in the light phase. These results attest to the chemosensitive function of the hypothalamic region comprising LH, LPeF, MPeF and DMH and suggest that the role of these areas in the central chemoreflex involves the orexinergic neurons, independently of the phase of the light-dark cycle, with the exception of the MPeF, that seems to have a subpopulation of orexinergic neurons that act especially in the light phase.